Forming The Skill To Fight Against Mass Culture In Youth With The Help Of The Heritage Of The Ancestors (Eurasian Journal of Humanities and Social Sciences, 2022)
The article highlights the problem of the spread of mass culture and its influence on the youth. The essence of the concept of mass culture is revealed, various assessments of this phenomenon are given. The discrepancy between the goals and content of the national culture of the Uzbek people and modern mass culture is especially emphasized. Born in the context of globalization. In this regard, the need to form among young people respect and pride in national spiritual values and the high culture of their people is determined